2016
DOI: 10.1007/s40830-016-0083-y
|View full text |Cite
|
Sign up to set email alerts
|

On the Transformation Behavior of NiTi Shape-Memory Alloy Produced by SLM

Abstract: Selective laser melting has been applied as a production technique of nickel titanium (NiTi) parts. In this study, the scanning parameters and atmosphere control used during production were varied to assess the effects on the final component transformation criteria. Two production runs were completed: one in a high (*1800 ppm O 2 ) and one in a low-oxygen (*220 ppm O 2 ) environment. Further solution treatment was applied to analyze precipitation effects. It was found that the transformation temperature varies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
56
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 113 publications
(59 citation statements)
references
References 20 publications
2
56
1
Order By: Relevance
“…[ 24 , 29 ]. It is worth mentioning that various optimized energy densities for NiTi alloys have been reported in literature, from 55 to 300 J/mm 3 [ 24 , 29 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 ]. An even higher energy density of 595 J/mm 3 was used by Ma et al [ 42 ], by reducing the hatch spacing.…”
Section: Introductionmentioning
confidence: 99%
“…[ 24 , 29 ]. It is worth mentioning that various optimized energy densities for NiTi alloys have been reported in literature, from 55 to 300 J/mm 3 [ 24 , 29 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 ]. An even higher energy density of 595 J/mm 3 was used by Ma et al [ 42 ], by reducing the hatch spacing.…”
Section: Introductionmentioning
confidence: 99%
“…In a separate study performed by Speirs et al, they reported that the oxygen content present during the fabrication process had a strong effect on the transformation characteristics of the SLM NiTi samples [35]. as the scanning speed increased [35]. Unquestionably, more studies are required to validate these contradictory findings.…”
Section: Effects Of Process Parametersmentioning
confidence: 99%
“…According to the information shown in [16,21,25,28] and the effect of process parameters [7,20,21,33,35] on the transformation characteristics, shape memory responses and mechanical properties of NiTi.…”
Section: Effects Of Process Parametersmentioning
confidence: 99%
See 2 more Smart Citations